The Influence of Ambient Temperature Changes on the Indicators of Inflammation and Oxidative Damage in Blood after Submaximal Exercise - Marta Pawłowska; Celestyna Mila-Kierzenkowska; Tomasz Boraczyński; Michał Boraczyński; Karolina Szewczyk-Golec; Paweł Sutkowy; Roland Wesołowski; Marlena Budek; Alina Woźniak (MDPI AG, 2022)
Physical activity has a positive effect on human health and well-being, but intense exercise can cause adverse changes in the organism, leading to the development of oxidative stress and inflammation. The aim of the study was to determine the effect of short-term cold water immersion (CWI) and a sauna bath as methods of postexercise regeneration on the indicators of inflammation and oxidative damage in the blood of healthy recreational athletes. Forty-five male volunteers divided into two groups: 'winter swimmers' who regularly use winter baths (n = 22, average age 43.2 ± 5.9 years) and 'novices' who had not used winter baths regularly before (n = 23, mean age 25 ± 4.8 years) participated in the study. The research was divided into two experiments, differing in the method of postexercise regeneration used, CWI (Experiment I) and a sauna bath (Experiment II). During Experiment I, the volunteers were subjected to a 30-min aerobic exercise, combined with a 20-min rest at room temperature (RT-REST) or a 20-min rest at room temperature with an initial 3-min 8 °C water bath (CWI-REST). During the Experiment II, the volunteers were subjected to the same aerobic exercise, followed by a RT-REST or a sauna bath (SAUNA-REST). The blood samples were taken before physical exercise (control), immediately after exercise and 20 min after completion of regeneration. The concentrations of selected indicators of inflammation, including interleukin 1β (IL-1β), interleukin 6 (IL-6), interleukin 8 (IL-8), interleukin 8 (IL-8), interleukin 10 (IL-10), transforming growth factor β1 (TGF-β1) and tumor necrosis factor α (TNF-α), as well as the activity of indicators of oxidative damage: α1-antitrypsin (AAT) and lysosomal enzymes, including arylsulfatase A (ASA), acid phosphatase (AcP) and cathepsin D (CTS D), were determined. CWI seems to be a more effective post-exercise regeneration method to reduce the inflammatory response compared to a sauna bath. A single sauna bath is associated with the risk of proteolytic tissue damage, but disturbances of cellular homeostasis are less pronounced in people who regularly use cold water baths than in those who are not adapted to thermal stress.